2020
DOI: 10.52547/vacres.7.2.49
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Inactivation of Infectious Bursal Disease Virus for Use as a Vaccine and Immunodiagnostic Reagent

Abstract: Introduction: Poultry vaccines are used to immunize chickens against different diseases. Inactivated vaccines have been widely used to protect poultry against diseases such as infectious bursal disease (IBD). IBD is one of the most important viral immunosuppressive diseases in the poultry industry. This viral disease targets the immune organs. This study was aimed to evaluate the effect of an inactivated IBDV antigen on inducing the humoral immune response in Specific-Pathogen-Free (SPF) chickens. Methods: An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Serum antibody titers were raised against IBDV in all treated groups as detected by ELISA. BEL-inactivated antigen generally showed much better antigenicity stability than other preparations (35).…”
Section: Vaccine Related Studiesmentioning
confidence: 91%
See 3 more Smart Citations
“…Serum antibody titers were raised against IBDV in all treated groups as detected by ELISA. BEL-inactivated antigen generally showed much better antigenicity stability than other preparations (35).…”
Section: Vaccine Related Studiesmentioning
confidence: 91%
“…All three antigen preparations were adjuvanted separately with ISA-70 and then injected SC in to groups of three-week-old SPF chickens. The results showed that the lowest concentrations that could fully inactivate the infectivity of the IBD virus were 2.5 mM for BEI, 0.15% for BPL and 0.1% for formalin (35). Inactivated preparations of 2.5 mM BEI and 0.15% BPL showed no apparent adverse effect on IBDV infectivity and showed a reliable inactivation unlike antigens inactivated with 0.1% formalin that demonstrated an antigenicity decrease after one year (35).…”
Section: Vaccine Related Studiesmentioning
confidence: 98%
See 2 more Smart Citations